The Influence of Emotional Intelligence on The Working Sphere of Life ("Journal "U". Economy. Management. Finance.", 2020)
The purpose of the study is to disclose such a concept as emotional intelligence and to determine the importance of this concept in the working sphere of life. The article considers the influence of emotional intelligence on the physical and moral component of the employee, and how much the concept of emotional intelligence affects the productivity of the employee and the team as a whole. Using the observations from this article, you can increase your productivity or even the productivity of yourself and your team. There are also a few useful things that can help reduce emotional stress.
Keywords: emotional Intelligence; soft-skills; hard-skills; manager; self-awareness; self-control